OPPORTUNITIES AND CHALLENGES FOR MICRO-SMALL AND MEDIUM BUSINESS IN INDONESIA FACING ASEAN ECONOMIC COMMUNITY - Raden Aswin Rahadi (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2016)
This research is a part of a continuous study to analyze the opportunities and challenges for micro-small and medium business in Indonesia when facing ASEAN Economic Community (AEC) in 2016. It has its own uniqueness, as it will combine the point of view between current business owners and current literature study synthesis on business perception towards AEC. Ten business owners have been interviewed. The results suggested AEC provides challenges for the business owners, particularly in terms of capital; competitiveness; sales system; innovation; finance, bureaucracy; and government preparedness. AEC also provides opportunities, in terms of market potential; creativity; export opportunities; business owners’ resistances and sustainability; and knowledge of local market. From all of the keywords mentioned by the respondents, there are four main attributes considered as important: human resources; creativities; market share; and capital. Finally, most of the respondents suggested that AEC will bring more positive influences for the development of micro-small and medium business in Indonesia.